Territorial features of migrant-phobia in the cities of the North Caucasus - Ivan Alekseevich Soloviev; Natalia Alexandrovna Chchitova (Наука. Инновации. Технологии, 2022)
In the article, based on the results of a sociological survey that includes mass surveys of indigenous people, interviews, focus groups and monitoring results of content analysis of ads with ethnic coloring in rental housing markets, the level of migrant-phobia in the cities of the North Caucasus is identified in comparison with the all-Russian background. The study conducted a theoretical review of scientific literature on migrant-phobia. The dependence of the migrant-phobia dynamics on the growth of obvious or potential threats to Russia, incl. terrorist situation. The study identiied a regional differentiation of the degree of migrant-phobia in the North Caucasus, primarily due to the peculiarities of the ethnic composition of the population of its regions. The study made it possible to determine the contemporary types of regions in the North Caucasus in terms of migrant-phobia. The article deines intraregional features of the degree of migrant-phobia in the North Caucasus, at the level of rural areas (municipalities) and cities. Important regularities of the level of migrant-phobia correlating with the type of settlements (urban and rural), as well as with the size of the city (millionaire, large, medium, small). The article developed measures of national and migration policy aimed at alleviating the problem of phobias and prejudices towards migrants in the regional host communities of the North Caucasus.